Pengaruh Pendapatan Margin Murabahah dan Pendapatan Bagi Hasil Musyarakah terhadap Laba Bersih - Ruhliandini, Putri Zafira; Yanthiani, Lenny (Jurnal Dimamu, 2024)
This murabahah financing product is also a product that is quite profitable for banks in developing working capital. Net profit is profit that has been reduced by costs that are a burden on the company in a certain period including taxes. With the increase in murabahah margin income and musyarakah profit sharing income, it will be able to increase the company's net profit. Net profit greatly influences the increase and decrease in profit which will indicate the company's performance. In this study, the author is interested in analyzing the factors that support net profit growth, as well as identifying strategies to increase efficiency and effectiveness to increase murabahah margin income and murabahah profit sharing income. The purpose of this study is to determine how much influence murabahah margin income and musyarakah profit sharing income have on the net profit of PT. BPRS Al-Ma'soem. This study uses a quantitative method with an explanatory approach to analyze the effect of murabahah margin income and musyarakah profit sharing income on the net profit of PT. BPRS Al-Ma'soem. Based on the results of the study, the variables of murabahah margin income and musyarakah profit sharing income have a positive and significant effect on net profit of 87%. Based on the calculation of SPSS 25.0 For Windows, the results in the data show Fcount> Ftable, namely, 29.799> 4.459, then Ha is accepted and H0 is rejected, which means that simultaneously there is a significant effect between murabahah margin income  and musyarakah profit sharing income  on net profit.